A dynamic energy savvy routing algorithm for mobile Ad-hoc and sensor networks - Mohamad Nazim, Jambli; Adnan Shahid, Khan; Halikul, Lenando; Jiwa, Abdullah; Sinarwati, Mohamad Suhaili (American Scientific Publishers, 2017)
Mobile Ad-hoc and Sensor Networks (MASNETs) are energy constrained networks which have been the focus of many recent research and development efforts. In MASNETs, the network topologies are frequently change due to the moving sensor nodes that have low radio frequency coverage which make the design and implementation of a routing protocol in this networks very challenging. Thus, the Dynamic Energy Savvy (DES-AODV) routing algorithm is proposed to enhance the performance of Ad-hoc On Demand Distance Vector (AODV) by changing the routing metric from hop count to estimated distance that is based on the Received Signal Strength Indicator (RSSI) values. The performance of DES-AODV is evaluated and compared with the existing AODV in terms of the average percentage of packet loss and energy consumption with the density of mobile nodes. The simulation results show that the proposed DES-AODV outperforms the existing AODV in both percentage of packet loss and energy consumption. © 2017 American Scientific Publishers All rights reserved.